The Impact of Kinetic Façade on the Performance and Energy Efficiency of a Public Building in Dubai - The Case of Dubai Frame - Alawaysheh, Areen (2019)
Recently many studies were conducted to discuss adaptive and intelligent façade techniques in response to climate factors to enhance the sustainability measures of buildings. However, these studies have not been interacted in the design stage of buildings especially in the cities of Dubai and Abu Dhabi, where there are many high-rise buildings that consist of large percentage of glazing in their façade, which increase the amount of energy consumption and affect the performance of these buildings. The aim of this research is to optimise the sustainability of a public building by applying a kinetic system and a design strategy that response to three indicators; electricity and cooling loads, sun exposure and the aesthetic values of the building. Moreover, this research validates the use of Integrated Environmental Solutions (IES VE software) to be accredited for Dubai Municipality green building evaluation system (Safat) in assessing the performance of buildings through the design process of innovative technologies, which is achieved by validating IES results in comparison to the conducted field measurements using a special equipment from the sustainability department of the British University in Dubai. This research introduces a new concept of shading systems and discusses the main parameters of kinetic design principles and strategies to generate an optimal solution and result in getting a better rating of the building through Sa'fat indicators. In addition, a basic model that consist of perforated fixed façade and a proposed model with kinetic shading system will be compared to demonstrate that the implementation of new innovative systems and techniques will be an efficient strategy to enhance the performance of the building while preserving its architectural concepts. The research has reached several important results. For example, the optimal kinetic system results in 20% energy savings and 31% reduction in daylighting illuminance levels while taking into account the current situation of the building and its aesthetic values. The results of this research will benefit engineers and designers to design buildings with efficient energy both inside the UAE and abroad from countries that has the same climatic conditions.